The relationship between mental fatigue and social responsibility among nurses who provided care to patients with coronavirus disease 2019: a cross-sectional study - Soheileddin Salmani; Mohammad Salehpoor Emran; Afsaneh Sadooghiasl; Shima Haghani; Shahzad Pashaeypoor (BMC, 2023)
Abstract Background and Aim Mental fatigue (MF) was a major challenge for nurses during the coronavirus disease 2019 (COVID-19) pandemic. Nurses' sense of responsibility towards their patients and societies may influence their MF. This study aimed to assess the relationship between MF and social responsibility (SR) among nurses who provided care to patients with COVID-19. Methods This cross-sectional descriptive-analytical study was conducted in 2021. Participants were 258 nurses randomly selected from eleven COVID-19 care hospitals in Tehran, Iran. Data were collected using three self-report instruments, namely a demographic questionnaire, the Mental Fatigue Scale, and the Social Responsibility Questionnaire. The SPSS software (v. 16.0) was used to analyze the data at a significance level of less than 0.05. Results The mean scores of MF and SR were 31.73 ± 7.35 and 3.45 ± 0.35, respectively. The highest and the lowest scored SR subscales were ethical responsibilities with a mean of 3.67 ± 0.42 and economic responsibilities with a mean of 2.93 ± 0.62. MF had a significant negative correlation with legal responsibilities and a significant positive correlation with economic responsibilities (P < 0.05). The only significant predictor of SR was financial status which significantly predicted 4.3% of the variance of SR (P < 0.05). Conclusion More than half of the nurses who provided care to patients with COVID-19 suffered from MF and their mental fatigue had a significant correlation with their legal and economic responsibilities. Healthcare authorities and policymakers need to develop programs to reduce nurses' MF and improve their satisfaction.